Proceedings of the First International Conference on Science, Technology, Engineering and Industrial Revolution (ICSTEIR 2020) 2021
DOI: 10.2991/assehr.k.210312.081
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tobacco on Health-Related Parameters in Chronic and Acute Healthy Male Smokers

Abstract: Ingestion of tobacco is detrimental to overall health that could affect the normal function of several health parameters in the human body. While it has been generally documented that smoking is injurious to health, the influence of tobacco on certain health parameters with regards to the duration of smoking in individuals without any apparent health issues is yet to be fully investigated. The current study investigated the effect of smoking on health parameters of healthy male smokers. A total of 107 (37 ± 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, studies have demonstrated that smokers who live a sedentary lifestyle have lower physical performance and lack of endurance, characterized by shortness of breath, all of which could lead to the deterioration of overall health [ 57 , 58 ]. Therefore, it is important to note that lack of PA coupled with smoking is a harbinger of many health complications such as cardiovascular diseases and cancer that may affect the general well-being and, indeed, mortality, of an individual [ 34 , 59 ]. However, the adverse effects of smoking on overall health have been shown to be mitigable or reversable when an individual quits smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have demonstrated that smokers who live a sedentary lifestyle have lower physical performance and lack of endurance, characterized by shortness of breath, all of which could lead to the deterioration of overall health [ 57 , 58 ]. Therefore, it is important to note that lack of PA coupled with smoking is a harbinger of many health complications such as cardiovascular diseases and cancer that may affect the general well-being and, indeed, mortality, of an individual [ 34 , 59 ]. However, the adverse effects of smoking on overall health have been shown to be mitigable or reversable when an individual quits smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Gender plays a significant role in the tendency to smoke in Malaysia, where the male-to-female ratio of smokers in the country is highly skewed: A larger proportion of smokers in the country are males, which could be attributed to the social norms, which are not favourable to female smoking [ 34 ]. Hence, the current study focused on adult male smokers only.…”
Section: Introductionmentioning
confidence: 99%